Hit-optimization using target-directed dynamic combinatorial chemistry: development of inhibitors of the anti-infective target 1-deoxy-d-xylulose-5-phosphate synthase. Issue 22 (6th May 2021) - Jumde, Ravindra P.; Guardigni, Melissa; Gierse, Robin M.; Alhayek, Alaa; Zhu, Di; Hamid, Zhoor; Johannsen, Sandra; Elgaher, Walid A. M.; Neusens, Philipp J.; Nehls, Christian; Haupenthal, Jörg; Reiling, Norbert; et al.
Abstract : Target-directed dynamic combinatorial chemistry was used for hit-identification and subsequent hit-optimization for the anti-infective target 1-deoxy-d -xylulose-5-phosphate synthase resulting in novel inhibitors with low micromolar affinities. Abstract : Target-directed dynamic combinatorial chemistry (tdDCC) enables identification, as well as optimization of ligands for un(der)explored targets such as the anti-infective target 1-deoxy-d -xylulose-5-phosphate synthase (DXPS). We report the use of tdDCC to first identify and subsequently optimize binders/inhibitors of the anti-infective target DXPS. The initial hits were also optimized for their antibacterial activity against E. coli and M. tuberculosis during subsequent tdDCC runs. Using tdDCC, we were able to generate acylhydrazone-based inhibitors of DXPS. The tailored tdDCC runs also provided insights into the structure–activity relationship of this novel class of DXPS inhibitors. The competition tdDCC runs provided important information about the mode of inhibition of acylhydrazone-based inhibitors. This approach holds the potential to expedite the drug-discovery process and should be applicable to a range of biological targets.